Employee Performance Analysis at UPT Puskesmas Simalingkar - Indah Doanita Hasibuan; Putri Dina; Sri Devi; Muhammad Ridwan; Sufiah Adena Putri (Universitas Ibn Khaldun Bogor, 2024)
Quality health services are very important to maintain the welfare of the community. The role of Puskesmas has significance in providing health services according to the needs of residents in an area. This research focuses on the Technical Implementation Unit (UPT) of Simalingkar Health Center in Medan. The performance of employees in this unit is a major factor in achieving health service standards. This study used a qualitative approach with a descriptive approach, involving participants from the puskesmas and patients who had received services at the Simalingkar Health Center. Data was collected through in-depth interviews with stakeholders. The results of research at the Simalingkar Puskesmas as a whole, both from the puskesmas and patients, that the performance of employees at the Simalingkar Puskesmas UPT is generally considered good. However, several aspects need to be improved at the Simalingkar Health Center. Such as improving the quality of patient care, communication training among fellow employees, and further evaluation of certain health programs. This recommendation can be used as a basis to continue to improve the quality of health services at the Simalingkar Health Center. It can be the basis for continuing to improve the quality of health services at Puskesmas Simalingkar, focusing on aspects that can have a positive impact on the community. Periodic evaluation of employee performance, patient involvement as the main stakeholder, and implementation of concrete improvements are expected to improve the effectiveness and efficiency of health services at the Simalingkar Health Center.